PELATIHAN WIRAUSAHA MUDA DALAM UPAYA MENINGKATKAN KUALITAS LULUSAN SISWA SMK MUHAMMADIYAH PARAKAN, TANGSEL - Ahmad Maulana Irfanudin; Erlita Kurniawaty; Ratih Andalusi (PENGABDIAN SOSIAL, 2023)
ABSTRACT The reason of this community benefit is to supply instruction to the understudies of Muhammadiyah Parakan Professional School around the significance of enterprise and getting to be a Youthful Business visionary as an alternative in building a trade. The strategy utilized there are a few stages counting the planning arrange, which incorporates the introductory study, stabilization and assurance of areas and targets. After the overview, the execution area and target members of the movement were decided. The following arrange is the execution organize of Community Benefit. At this arrange, preparing will be given to understudies of SMK Muhammadiyah on the stages of getting to be a youthful business person and the tips for getting to be a fruitful business person. Preparing is carried out by giving an outline of enterprise, mentoring and a address and reply session. The result of this action is to supply understudies with an understanding of how a commerce begins, the utilize of the Commerce Demonstrate Canvass (BMC) in arranging, channeling, an outline of costs to pay from business enterprise. Community Benefit this time is focused on at Muhammadiyah Parakan Professional Tall School understudies who have different foundations in consider programs, counting bookkeeping, Bookkeeping, Online Promoting to Interactive media, so it is trusted that through this program shaped, Muhammadiyah Professional School understudies will be more propelled to create their commerce concurring to their individual interface. Keywords: Young Entrepreneur, Business Model Canvas, Marketing